Comparative transcriptomic analysis provides insights into antibacterial mechanisms of Branchiostoma belcheri under Vibrio parahaemolyticus infection. Issue 76 (May 2018) - Zhang, Qi-Lin; Zhu, Qian-Hua; Liang, Ming-Zhong; Wang, Feng; Guo, Jun; Deng, Xian-Yu; Chen, Jun-Yuan; Wang, Yu-Jun; Lin, Lian-Bing
Abstract: Amphioxus, a basal chordate, is widely considered to be an existing proxy of the invertebrate ancestor of vertebrates, and it exhibits susceptibility to various pathogen infections and pathogenic mimic challenges. Here, in order to understand more clearly its antibacterial mechanisms, we analyzed the ribosomal RNA (rRNA)-depleted transcriptome of Chinese amphioxus ( Branchiostoma belcheri ) infected with Vibrio parahaemolyticus ( V. p. ) via next-generation deep sequencing technology (RNA-seq). We identified a total of 3214 differentially expressed genes (DEGs) by comparing V. p. -infected and control transcriptome libraries, including 2219 significantly up-regulated and 995 significantly down-regulated DEGs in V. p. -infected amphioxus. The DEGs with the top 10 most dramatic expression fold changes after V. p. infection, as well as 53 immune-related DEGs (IRDs) belonging to four primary categories of innate immunity were analyzed further. Through gene ontology (GO) and pathway enrichment analysis, DEGs were found to be primarily related to immune processes, apoptosis, catabolic and metabolic processes, binding and enzyme activity, while pathways involving bacterial infection, immune signaling, immune response, cancer, and apoptosis were overrepresented. We validated the RNA-seq results by detecting the expression levels of 10 IRDs using qRT-PCR, and we surveyed the dynamic variation in gene expression for these IRDs at 0, 6, 12, 24, and 48 h after V. p. treatment. Subsequently, according to the RNA-seq results, the presence of a primitive Toll-like receptor (TLR)-mediated antibacterial immune signaling pathway was predicted in B. belcheri . This study provides valuable information regarding antibacterial immunity for further research into the evolution of immunity in vertebrates and broadens our understanding of the innate immune response against bacterial invasion in amphioxus. Highlights: We sequenced the transcriptomes of Branchiostoma belcheri after Vibrio parahemolyticus treatment. We obtained 3214 differently expressed genes (DEGs) between control and treatment. We screened 53 immune-related DEGs (IRDs) after V. parahemolyticus treatment. Validation of DEGs and expression survey of IRDs at the different time points was conducted by qRT-PCR. We predicated the possibly chordate-primitive TLR signaling pathway in B. belcheri.